Bioactive Properties of Probiotic and Prebiotic Edible Films - Medeiros, Jackson A. [UNESP]; Niro, Carolina M.; Salgaço, Mateus K. [UNESP]; Sivieri, Kátia [UNESP]; Azeredo, Henriette M. C. (Springer Nature, 2024)
Edible films have been increasingly studied as carriers for bioactive components, including probiotic microorganisms and/or prebiotic compounds. Whereas the incorporation of prebiotic compounds does not usually require wide modifications to the usual processing protocols to produce edible films, the addition of live microorganisms requires special attention when it comes to processing conditions, in order to assure that their viability is preserved as much as possible. In this chapter, we describe the basic procedures for obtaining probiotic and/or prebiotic edible films as well as the specific determinations that are required to properly characterize them in terms of their bioactive properties and stability.